THE EFFECT of GA3 AND SALINITY on GROWTH of ROSELLE (Hibiscus sabdariffa L.) - Novita, Aisar; Basyuni, Mohammad; Cemda, Abdul Rahman; Nora, Silvia; Mariana, Merlyn (International Journal of Biosciences and Biotechnology; Vol 8 No 2 (2021): International Journal of Bioscience and Biotechnology, 2021)
In order to alleviate the deleterious effects of salinity, different types of phytohormones have been used. Among them, GA 3 has been the main focus of some plant scientists. This study aimed to evaluate the effect of gibberellic acid and salinity on growth and production of roselle ( Hibiscus sabdariffa L). This research was conducted in a greenhouse of Agriculture Faculty, University of Sumatera Utara, Medan. The study used utterly randomized design with two factors. The first factor was gibberellic acids. They were gibberellic acid (5 mg L -1 ) and no gibberellic acid. The second factor was salinity. They were 0 dsm -1 and 4-5 dsm -1 . The interaction between gibberellic acid and salinity acid indicated a significant effect on the percentage of germination, chlorophyll a and b and beta-carotene. The application of giberellic acid helped in the tolerance of plants to salinity. Thus, application of GA 3 become essential to improve overall productivity in salinity.